(untitled) (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY Hereditary haemochromatosis is a genetic disease characterised by progressive accumulation of iron in organs leading to many unspecific complaints, but even today diagnosis may be delayed. We aimed to identify symptoms associated with iron overload and parameters typical in patients with hereditary haemochromatosis which might help to facilitate detection and diagnosis in daily clinical routine. METHODS We analysed the prospective Swiss Haemochromatosis Cohort (SHC), including 163 patients for whom serum ferritin levels at diagnosis were available. The cohort was stratified according to the degree of iron overload. Substantial iron overload was defined as serum ferritin concentrations ≥1000 µg/ml. RESULTS Patients with substantial iron overload had significantly higher liver enzymes (p <0.001) and more often arthropathy of the metacarpophalangeal joints (p <0.001) and upper ankle joint (p = 0.003). Elevated liver enzymes, especially elevated alanine aminotransferase (ALT) levels, were associated with a 10.1-fold (95% confidence interval [CI] 4.8–21.2) increased the risk for serum ferritin levels ≥1000 µg/ml. Furthermore, metacarpophalangeal joint arthropathy emerged as an important predictor for iron overload with a 3.6-fold increased risk (95% CI 1.8–7.1; p <0.001). Only elevated ALT levels and metacarpophalangeal joint arthropathy remained significantly associated with elevated iron levels after adjustment for possible confounders in patients diagnosed with hereditary haemochromatosis. CONCLUSION Elevated ALT levels and metacarpophalangeal arthropathy remained independently associated with elevated ferritin levels in patients with haemochromatosis and should prompt clinicians to consider iron overload in patients with hereditary haemochromatosis.